Countries with public dental care coverage have lower social inequalities in the use of dental services than countries without such coverage - Listl, Stefan (The journal of evidence based dental practice, 2015)
This study was based on data from wave 2 of the Survey of Health, Ageing, and Retirement in Europe (SHARE). The study sample comprised 12,364 men and 14,692 women age 50 years or older from 11 European countries (Austria, Belgium, Denmark, France, Germany, Greece, Italy, Netherlands, Spain, Sweden, and Switzerland). SHARE data from Ireland were excluded because no sampling weights were available for Ireland.
Available online 15 December 2014
Gesehen am 18.06.2020